Directed Reading Thinking Activity (DRTA) to Improve Reading Comprehension for 7th Grade Students at SMP Negeri 1 Surabaya - Suparman (JournEEL, 2021)
The purpose of this research was to increase students' achievement in reading comprehension by implementing the Directed Reading Thinking Activity (DRTA) strategy to the 7th grade students at SMP Negeri 1 Surabaya in the academic year 2020/2021. Each cycle of classroom action research consisted of three meetings and included four steps: planning, action, observation, and reflection. The data were gathered through the use of two instruments: observation and test. The results indicated that students made great progress in their ability regarding to the reading comprehension. Pre-test mean score was only 67.28, but improved to 72.42 in cycle I and 81.22 in cycle II. The pre-test of the highest score was only 78 and improved to 82 to 90 in subsequent cycles. Meanwhile, the lowest pre-test score was 60, and the lowest post-test score ranged from 62 to 68. In case of the students who passed the tests, while only 6 students (16.67%) passed the pre-test, there were significant improvements in post-tests, with 12 students (33.33%) passing in post-test cycle I and 29 students (80.56%) passing in post-test cycle II. This research was stopped in cycle II due to the fact that the criteria for success were met in a percentage of 80.56%, with 29 students passing the post-test in cycle II, based on the Minimum Mastery Criteria (KKM) standard of > 76.